The Influence of Sehat Jiwa Education on the First Active Phase of Labor in Community Health Centers across Makassar City - Marwang, Sumarni; Passe, Rosita; Triananingsih, Nurhidayat; Kusniyanto, Rahayu Eriyanti (Al-Sihah : The Public Health Science Journal, 2023)
During pregnancy, women commonly experience both psychological and emotional changes, leading to concerns about childbirth and potential labor complications. Therefore, education programs became essential for preparing mothers mentally for delivery with the engagement of health workers and families. This study aimed to assess the effectiveness of Sehat Jiwa education on the length of the first active stage of labor. Using a Quasi-experimental design with a two-group control approach, the sample comprised 64 respondents (34 in the intervention group and 30 in the control group). The instruments adopted were the Sehat Jiwa (English: Soul Health) education module, questionnaires, and partograph sheets. The results showed that there was no significant difference in the length of the first active phase between the intervention and control groups, with a p-value of 0.061 > 0.05. However, the average duration for the intervention group (5.88 hours) was slightly shorter than the control group (6.40 hours). Emphasizing Sehat Jiwa-based education for pregnant women was crucial, fostering smoother delivery processes and reducing the likelihood of increased labor complications.